2013
DOI: 10.3109/14756366.2013.840614
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profiling and in vitro biological effects of Cardiospermum halicacabum L. (Sapindaceae) aerial parts and seeds for applications in neurodegenerative disorders

Abstract: Cardiospermum halicacabum is widely used in traditional medicine. Previous studies have focused on the aerial parts, while the seeds have been poorly investigated. This work aimed to analyse the chemical composition of extracts from aerial parts and seeds obtained using Naviglio and Soxhlet (PN, PS, and SN, SS, respectively), the inhibitory properties against tyrosinase, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) and the antioxidant effects. PN total extract showed significant anti-tyrosinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Cholinesterase inhibitors are currently used as a drug for the treatment of AD. The inhibitors increase brain acetylcholine (ACh) levels by preventing the breakdown of ACh and this case is very important to cognitive function (Menichini et al, 2014 ). Again, α-amylase and α-glucosidase release glucose from larger carbohydrates (especially starch) and are key enzymes in DM glucose level control (Kubinova et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cholinesterase inhibitors are currently used as a drug for the treatment of AD. The inhibitors increase brain acetylcholine (ACh) levels by preventing the breakdown of ACh and this case is very important to cognitive function (Menichini et al, 2014 ). Again, α-amylase and α-glucosidase release glucose from larger carbohydrates (especially starch) and are key enzymes in DM glucose level control (Kubinova et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The extract of C. halicacabum was analyzed for its total phenol and flavonoid content as previously described. 9 …”
Section: Methodsmentioning
confidence: 99%
“…Several chemical constituents have been isolated from its, ie, β-arachidic acid, apigenin, apigenin-7- O -glucuronide, chrysoeriol-7- O -glucuronide, rutin, and luteolin-7- O -glucuronide. 7 9 Various fatty acids were also isolated from seed oil. 10 The plant-based herbal products like gel, cream, shampoo, spray, medical drops, and pills are commercially available and are helpful in dry itchy skin and scalp and in the treatment of chronic skin diseases, including psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extracts also showed a myocardial depressive effect similar to that obtained with cholinergic agents, which was partially blocked by atropine. [39][40][41][42][43] Some research has shown antimalarial activity of the extracts of this plant as well as anti-inflammatory and analgesic, antiparasitic, anti-diarrheal, anti-diarroil, antihysterility, anti-sterility, nephroprotective; hepato-protective and anticancer activity. [44][45][46][47][48][49][50][51][52]…”
Section: Pharmacological Activitymentioning
confidence: 99%